Determinants of Recent HIV Self-Testing Uptake Among Men Who Have Sex With Men in Jiangsu Province, China: An Online Cross-Sectional Survey - Li, Jianjun; Marley, Gifty; Zhang, Ye; Chen, Yunting; Tang, Weiming; Rongbin, Yu; Fu, Gengfeng (Frontiers in Public Health, 2021)
Background: To help inform HIVST upscale, we assessed the determinants of recent HIVST uptake among men who have sex with men MSM in Jiangsu province, China. Methods: We conducted a convenience online survey from March to April 2020 among men ≥16 years who had ever had sex with other men. Statistical analysis included Pearson’s chi-square test, bivariate correlation and multivariable logistic regression. P-value < 0.05 was considered statistically significant. Results: Of the total 692 participants, 69.5%(481) were aged between 18-40 years, and 65.9%(456) had ever self-tested. Using HIVST for first HIV test (aOR=1.97, 95% CI:1.20-3.23), and perceiving HIVST as more private (aOR=1.53, 95% CI:0.93-2.52) and users not needing to go to a health facility (aOR=1.61, 95% CI:1.17-2.22) as facilitating factors were associated with recent HIVST. Conclusion: HIVST uptake rate has increased among Jiangsu MSM and can be further promoted by healthcare workers routinely recommending HIVST to their clients.